Metodologi Penelitian Psikodiagnostika - Rahmat Hidayat; Indira Primasari (Buletin Psikologi, 2011)
The measurements conducted in the discipline of psychology are related to the goals of pure andapplied sciences. Measurements taken for pure science is in general carried out within scientificresearches. Regarding those in the applied science, there are two methods, namely screening anddiagnosis that are commonly used in the practice of clinical measurement. This paper aims toaddress the comprehensive measurements required in the field of clinical measurement. Inparticular, it will discuss if psychometric properties only are already sufficient or they are, in fact,not needed in this field. In addition, it will also briefly describe the methodology of measuring thequality of instruments of clinical measurement.